Algal Lectins and their Potential Uses - Praseptiangga, Danar (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2015)
Lectins (hemagglutinins), or carbohydrate-binding proteins, are ubiquitous in nature and play important roles in many biological processes. They bind mono- and oligosaccharides reversibly with high specificity, but are devoid of catalytic activity, and in contrast to antibodies, are not products of an immune response. The erythrocyte agglutination or hemagglutination activity of lectins is a major attribute of these proteins and is used routinely for their detection and characterization. Due to their biochemical and biological properties, lectins attract a great deal of attention in the fields of medicine, molecular biology, biochemistry, and glycobiology. Lectins have been isolated and characterized from marine algae. Many of algal lectins generally have common characteristics of low molecular weight, no divalent cations requirements for their activity, and have an affinity for glycoproteins but not for monosaccharides. These properties imply that they may possess molecular structures and carbohydrate-binding specificities distinct from known lectins from other sources. Recent investigations revealed that algal lectins have the strict binding specificity to some definite oligosaccharide structures and are grouped into several types on the basis of oligosaccharide-binding specificity. Thus, marine algae are promising sources of novel lectin molecules for basic research and application. In spite of the progress made in biochemical characterization of algal lectins, additional information are still needed for a more comprehensive understanding of their molecular structures and possible biological functions for the future applications.